PERNIKAHAN DIBAWAH UMUR - Jamilah, Fitrotin; Evendi, Wakid; Sunardi, Sunardi (Jurnal Kajian Hukum Islam, 2018)
Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family or household based on the supreme divinity. And as for underage marriage according to law is marriage that is not in accordance with the marriage law chapter 11 article 1 verse 1 which states  that marriage can only be permitted if the male has reached the age of 19 years and the women has reached the age of 16 years. Thus if marriage under the age determined by the law, the marriage is underage. As for the purpose of this study id to discuss about 1) the definition of underage marriage according to the law, 2) the factors that cause underage marriage, 3) the impact of underage marriage, and 4) how to overcome and reduce the existence underage marriage. Explanation of the 4 discussion abavoe will help us to understand and add to our insights into underage marriage according to the law the causal factors and even the impact and how to overcome the problem